Concentration Bancaire, Structure Du Systeme Financier et Offre du Cr#xE9;dit Bancaire A Long Terme Dans la Zone Franc CFA (Global Journal of Management and Business Research, 2020)
The aim of this study is to determine the impact of bank concentration and financial structure on the long-term bank lending in the countries of the CFA franc zone over the period 2006-2016. We used a static panel data model and the random effectsestimat or. Firstly, we find that banking concentration in this area has a negative and significant impact on the long-term bankcred it supply. Secondly, we observe that the structure of the financial system also has a negative effect on long-term bank loans supply in this space. Based on these results, we re commend that public and onetaryauthorities encourage the widening of competition with in the banking sector and promote the simultaneous development of banking sectors and stock markets.
Keywords: bank concentration; financial structure; longterm bank cred it supply